User's guide to the information age a straight-talking guide to how our world is connected and how information shapes our lives - Morris, Kenneth M. (Lightbulb Press, 1999)
This guide provides a visual tour of the information age. The reader can explore the key information and the fun sidelines about telecommunications, computers, and the Internet, learning how they work, why they matter, and what the pros and cons of each high-tech tool are.